Conversion of biomass to chemicals using ionic liquids - Khan, A.S. (Elsevier Inc., 2019)
From the conversion of lignocellulosic biomass to platform chemicals using ionic liquids (ILs), it was concluded that ILs have dual functions and can be used as catalyst and solvent for the synthesis of 5-hydroxymethylfurfural (5-HMF) and levulinic acid (LA) from lignocellulosic biomass. The conversion of lignocellulosic biomass to chemicals depends upon the nature of feedstocks and structure of ILs. The yield of 5-HMF and LA from fructose and glucose is higher than cellulose and lignocellulose. Among the various available ILs, the acidic ionic liquids (AILs) such as C3SO3HmimHSO4, C4SO3HmimHSO4, C3SO3HmimCH3SO3, C3SO3HmimCl, C3SO3HmimCF3SO3, and C3SO3HPyHSO4 showed better yield of 5-HMF and LA. The imidazolium-based ILs that contain acidic functional group such HSO4 and Cl anion resulted in higher yield of LA and 5-5-HMF, respectively. Therefore it is essential to synthesize such ILs that have acidic functional group in their structure for the direct conversion of cellulose and lignocellulosic biomass to 5-HMF and LA. Â© 2020 Elsevier Inc. All rights reserved.